Bioindicadores de qualidade do solo no crescimento inicial de eucalipto sob fertilização organomineral à base de torta de filtro de cana-de-açúcar - Delvaux, Julio Cesar (2019)
The supply of mineral fertilizers provides production gains that can be adverse on soil quality. In this context, biofertilizer peletizados fertilizers (FOMs) to the base of filter cake of sugar cane compete as a promising alternative and sustainable for the fertilization of plantations, however little is known about the effect of the FOMs in the initial growth of eucalyptus and on soil quality. The objective of this work was to evaluate the morphophysiological response of eucalyptus plants, soil pH, the soil microbial biomass and activity resulting from the inflow of FOMs. An experiment was conducted in a greenhouse in vases with Red Latosol and seedlings of the hybrid Eucalyptus urophylla x Eucalyptus grandis (Clone I144) using the randomized blocks design in a subdivided plot scheme, and the effects of the different doses of FOM (0%, 50%, 100%, 150% and 200%) and a mineral treatment (100%) in relation to the dose of fertilizers recommended for the crop and in the subplots, the effects of the time (30, 60, 90 and 120 days after transplanting - DAT). It was found that the addition of the FOM leads to an initial increase of soil pH with subsequent reduction of the variable values. The highest increments of height, stem diameter, fresh and dry mass of leaves, stems and roots were observed for the dose 50%. The highest values of chlorophyll a were estimated for the doses 159%, 153% and 118% at 30, 90 and 120 DAT. The carbon values of biomass were inversely proportional to the doses of FOM and the values of basal respiration and metabolic quotient observed in the treatments 50% and 100% equal or better to those observed in the treatment with mineral fertilizer. Pelletized organomineral fertilizers based on filter cake do not provide damage to carbon and microbial biomass activity of the growing soil of E. urophylla x E. grandis, presenting itself as possible substitutes of mineral fertilization for the implantation of eucalyptus forests.